1996
DOI: 10.1113/jphysiol.1996.sp021308
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensitive medullary neurones in the brainstem‐‐spinal cord preparation of the neonatal rat.

Abstract: 1. Using the isolated medulla and spinal cord of the neonatal rat, the response to CO2 -induced changes in superfusate pH was examined in whole cell and perforated patch recordings from ventral medullary neurones which were identified by injection of Lucifer Yellow. The respiratory response to changing the CO2 concentration (from 2 to 8%) consisted of an increase in phrenic burst frequency, which could be accompanied by an increase, decrease or no change in burst amplitude. 2. Five classes of neurone -inspirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
114
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(122 citation statements)
references
References 33 publications
7
114
0
1
Order By: Relevance
“…These cells are known to be intrinsically CO 2 chemosensitive, as their CO 2 chemosensitivity is retained after blockade of the synaptic transmission (Oyamada et al 1998;Wang et al 1998;Filosa and Putnam 2003;Severson et al 2003;Mulkey et al 2004). Since certain respiratory neurons postsynaptic to these cells are also intrinsically CO 2 chemosensitive (Kawai et al 1996), our finding of selective connections among the CO 2 -stimulated neurons in the cultured neuronal networks supports these previous studies. Such a preferential connection among CO 2 -stimulated neurons may underscore the necessary neuronal networks for the enhancement of CO 2 chemosensitivity by neurotransmission.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These cells are known to be intrinsically CO 2 chemosensitive, as their CO 2 chemosensitivity is retained after blockade of the synaptic transmission (Oyamada et al 1998;Wang et al 1998;Filosa and Putnam 2003;Severson et al 2003;Mulkey et al 2004). Since certain respiratory neurons postsynaptic to these cells are also intrinsically CO 2 chemosensitive (Kawai et al 1996), our finding of selective connections among the CO 2 -stimulated neurons in the cultured neuronal networks supports these previous studies. Such a preferential connection among CO 2 -stimulated neurons may underscore the necessary neuronal networks for the enhancement of CO 2 chemosensitivity by neurotransmission.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, they are presynaptic with respect to respiratory premotoneurons and motoneurons. Since the latter neurons are also CO 2 chemosensitive (Onimaru et al 1989;Kawai et al 1996; Talley et al 2000;Okada et al 2002; Guyenet et al 2005a;Kawai et al 2006), there may be synaptic interactions between the pre-and postsynaptic neurons allowing the necessary CO 2 signal amplification. Indeed, our recent studies have shown that both pre-and postsynaptic neurons contribute to the CO 2 chemosensitivity of cultured brainstem neurons (Su et al 2007).…”
Section: Nih Public Accessmentioning
confidence: 99%
“…15,17,18 All experimental protocols were approved by our facility's institutional review board. WKY and SHR pups (1 to 4 days old) were deeply anesthetized with ether, and the brainstem and spinal cord were isolated at the Th10 level.…”
Section: Intracellular Recordingsmentioning
confidence: 99%
“…Phrenic nerve activity was recorded simultaneously (Figure 1a). The RVLM neurons with discharges that were synchronized with phrenic activity were assumed to be respiratory neurons 17,18 and were excluded from this study. Membrane potentials were corrected for junctional potentials at the tip of the pipette (Ϫ11 mV).…”
Section: Intracellular Recordingsmentioning
confidence: 99%
“…Biphasic expiratory neurones (biphasic E) are characterized by preand post-inspiratory excitation and inspiratory-related inhibition (Onimaru et al 1990). Inspiratory neurones were further classified into three subtypes according to previous classifications performed with this preparation (Onimaru et al 1996(Onimaru et al , 1997 (Vm) were not corrected for liquid junction potentials, determined to be û −10 mV, in order to facilitate comparisons with earlier studies performed with this preparation Ballanyi et al 1994;Kawai et al 1996;Onimaru et al 1996Onimaru et al , 1997. The current-voltage (I-V) relationship was determined by injection of an inward current (0·02-0·08 nA, duration 100 ms) during silent phases between bursts in the expiratory phase of the respiratory cycle, or during negative holding potentials (−50 mV) in the case of certain expiratory neurones.…”
Section: Recordingsmentioning
confidence: 99%